2014
DOI: 10.2147/opth.s58413
|View full text |Cite
|
Sign up to set email alerts
|

Short-term intraocular pressure changes after intravitreal injection of bevacizumab in diabetic retinopathy patients

Abstract: BackgroundThis study examined the changes in short-term intraocular pressure (IOP) in a prospective series of patients undergoing intravitreal bevacizumab injection. The aim was to evaluate the frequency and predictive factors related to intraocular pressure (IOP) elevation in patients receiving intravitreal bevacizumab.Patients and methodsThis study included 52 patients with diabetic retinopathy between 28 to 75 years of age with a mean age of 51 years; 30 (58%) were females, and 22 (42%) were males. All pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 15 publications
5
18
0
1
Order By: Relevance
“…The IOP decreased rapidly over the next 30 min (Fig. 1) and the mean IOP at 30 min before removal of the needle was 14.67 ± 2.46 mmHg, which was similar to the reported IOP observed 30 minutes after intravitreal injection789101115.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The IOP decreased rapidly over the next 30 min (Fig. 1) and the mean IOP at 30 min before removal of the needle was 14.67 ± 2.46 mmHg, which was similar to the reported IOP observed 30 minutes after intravitreal injection789101115.…”
Section: Resultssupporting
confidence: 85%
“…In recent years, numerous studies have reported an acute volume-related intraocular pressure (IOP) elevation after intraocular injections56789101112131415. Lemos-Reis et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The implication of crystalline lens status continues to be discussed in the literature: some studies found a different IOP profile between phakic and pseudophakic patients, whereas others did not [3,7,12,13]. Contrary to our study, Kerimoglu et al [3] found a greater IOP increase in phakic patients than in pseudophakic patients 10 min after a 0.1-ml IVI of triamcinolone, which could raise the hypothesis of transient iridocorneal angle closure for this injected volume.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that in most patients IOP returns to safe levels within 30 min after IVI [19-27]. It has been reported, that 89% of patients receiving intravitreal ranibizumab experienced an IOP rise of more than 30 mm Hg at 5 s after injection [23], approximately one third after the first 5 min [16].…”
Section: Considerations Before Injectionmentioning
confidence: 99%